The potential of 1.5 T magnetic resonance imaging for the evaluation of fetal anomalies of the great vessels - Xie, Linjun; Xu, Hong; He, Xuelian; Fu, Hang; Zhang, Lu; Bai, Wei; Li, Xuesheng; Bao, Li; Xu, Huayan; Li, Xiaohong; Guo, Yingkun (Frontiers in Pediatrics, 2023)
Purpose To determine the efficacy of 1.5 T magnetic resonance imaging (MRI) for the diagnosis of anomalies of the fetal great arteries with comparison to fetal ultrasound, and to compare image quality between 1.5 T and 3.0 T MRI in fetal imaging of the great arteries. Methods We compared the results of postnatal exam or surgery and evaluated the application value of prenatal 1.5 T MRI in the assessment of fetal great-vessel anomalies. To further determine the diagnostic potential of 1.5 T MRI, 23 pregnant women with suspected fetal cardiovascular abnormalities who had undergone ultrasound and 3.0 T MRI were enrolled and compared, respectively. Results Prenatal MRI was superior to ultrasound in demonstrating aortic arch and branch abnormalities (sensitivity, 92.86% vs. 83.33%; specificity, 66.67% vs. 20%). The mean quality ratings for fetal MRI at 1.5 T was higher than 3.0 T (P < 0.001). Other than the fast scan speed afforded by 3.0 T MRI, the signal noise ratio (SNR) of 1.5 T MRI were higher than those of 3.0 T MRI; however, the difference in contrast to noise ratio (CNR) between the two imaging modalities was not statistically significant. Conclusions 1.5 T MRI can achieve an overall assessment of fetal great-vessel anomalies, especially aortic arch and branch abnormalities. Therefore, 1.5 T MRI can be considered a supplementary imaging modality for the prenatal assessment of extracardiac great vessels malformations.